Defining the minimum anatomical coverage required to protect the axilla and arm against penetrating ballistic projectiles. Issue 4 (23rd June 2015) - Breeze, Johno; Fryer, R; Lewis, E A; Clasper, J
Abstract : Introduction: Defining the minimum anatomical structural coverage required to protect from ballistic threats is necessary to enable objective comparisons between body armour designs. Current protection for the axilla and arm is in the form of brassards, but no evidence exists to justify the coverage that should be provided by them. Method: A systematic review was undertaken to ascertain which anatomical components within the arm or axilla would be highly likely to lead to either death within 60 min or would cause significant long-term morbidity. Results: Haemorrhage from vascular damage to the axillary or brachial vessels was demonstrated to be the principal cause of mortality from arm trauma on combat operations. Peripheral nerve injuries are the primary cause of long-term morbidity and functional disability following upper extremity arterial trauma. Discussion: Haemorrhage is managed through direct pressure and the application of a tourniquet. It is therefore recommended that the minimum coverage should be the most proximal extent to which a tourniquet can be applied. Superimposition of OSPREY brassards over these identified anatomical structures demonstrates that current coverage provided by the brassards could potentially be reduced.